QoS Aware Service Scheduling Scheme for VANETs - Ajay Guleria; Kuldip Singh; Narottam Chand (International Journal of Distributed Sensor Networks)
People immediately want to access the required data in vehicular ad hoc networks (VANETs). They provide the requests to road side unit (RSU) while travelling. The job of RSU is to handle various requests in such a way so that the service ratio and the quality of service (QoS) is optimized. In this paper we present a mechanism to achieve this goal. Our proposed algorithm considers both data size and deadline and optimizes uploading/downloading based on number of requests to be handled. It also deals with the impact of missed upload operations to achieve maximum optimization. The proposed scheme categorizes data into two classes to assign weight according to their effect on QoS and assigns priorities to upload and download requests while maintaining common queue for both upload and download requests. Simulation results corroborate that the proposed algorithm provides better service ratio and QoS than existing techniques.